2023
DOI: 10.3390/life13061334
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Radiofrequency and Platelet Rich Plasma in Degenerative Joint Arthritis: Two Case Reports and Literature Analyses

Abstract: (1) Background: Osteoarthritis (OA) is a debilitating joint disease. The are several therapies available for OA. According to current knowledge, the combination of Platelet-Rich Plasma (PRP) and Pulsed Radiofrequency (PRF) can be applied in the treatment of pain of nociceptive origin due to peripheral tissue damage. (2) Methods: We performed a narrative review identifying the articles by searching electronic databases. A retrospective analysis of patients with OA treated with PRF and PRP in “Vito Fazzi” Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…PRP is a concentrated solution of platelets that is rich in growth factors, showing the ability to facilitate angiogenesis, neuroprotection, neural regeneration, regulation of inflammation with broad therapeutic applications [17,[32][33][34][35][36][37][38][39][40][41][42]. Comparative studies have shown the clinical advantages of PRP injection for patients with incomplete RC tears.…”
Section: Discussionmentioning
confidence: 99%
“…PRP is a concentrated solution of platelets that is rich in growth factors, showing the ability to facilitate angiogenesis, neuroprotection, neural regeneration, regulation of inflammation with broad therapeutic applications [17,[32][33][34][35][36][37][38][39][40][41][42]. Comparative studies have shown the clinical advantages of PRP injection for patients with incomplete RC tears.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) is a preparation that is rich in platelets, fibrinogen, fibrin, chemokines and leukocytes with a platelet concentration of at least 1 000 000 platelets/μl, which is usually five-times higher than normal levels. 1 PRP offers anti-inflammatory and regenerative properties through angiogenesis, cell differentiation and proliferation. 2 Traditionally, PRP was mainly derived from adult peripheral blood and was used for the treatment of autologous diseases.…”
Section: Introductionmentioning
confidence: 99%